2020
DOI: 10.1021/acs.macromol.0c01423
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and Rheological Properties of Vitrimers: A Hybrid Molecular Dynamics and Monte Carlo Simulation Study

Abstract: Contrary to thermosets, vitrimers adjust their topology upon heating without loss of network integrity. Here, the proposed simulation methodology utilizes coarse-grained molecular dynamics in conjunction with a Monte Carlo method to capture the network integrity and flowability of vitrimers at high temperatures. The model vitrimer shows two transition temperatures. In addition to the conventional glass transition temperature, the topology freezing temperature is detected from the volumetric and rheological dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 62 publications
4
94
0
Order By: Relevance
“…Now we turn our attention to the timescale of the bond exchanges, and to better understand the impact of the lifetime of the exchangeable bonds on the dynamic and mechanical properties of the vitrimer, we compute the following autocorrelation function: C()ttrue˜=Httrue˜+truet˜0Httrue˜0H()truet˜02, where H()ttrue˜ represents a binary function. If two pairs of crosslinking beads are connected at a time interval t, then H()ttrue˜=1, otherwise H()ttrue˜=0 53,70 . This correlation function represents the lifetime of the exchangeable bonds that corresponds to the elementary exchange time inside the vitrimer melt 53 …”
Section: Resultsmentioning
confidence: 99%
“…Now we turn our attention to the timescale of the bond exchanges, and to better understand the impact of the lifetime of the exchangeable bonds on the dynamic and mechanical properties of the vitrimer, we compute the following autocorrelation function: C()ttrue˜=Httrue˜+truet˜0Httrue˜0H()truet˜02, where H()ttrue˜ represents a binary function. If two pairs of crosslinking beads are connected at a time interval t, then H()ttrue˜=1, otherwise H()ttrue˜=0 53,70 . This correlation function represents the lifetime of the exchangeable bonds that corresponds to the elementary exchange time inside the vitrimer melt 53 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, understanding of the rheological features is essential because these are related to the materials processing, which is currently underway in conjunction with theoretical points of view [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the wide range of timescales in vitrimer systems makes it difficult to use standard atomistic molecular simulations, Perego and Khabaz overcame this barrier by employing hybrid MD/MC simulations to study expansion and chain diffusivity around T v . 69 Using coarse-grained MD, Sciortino et al found that the macroscopic vitrimer viscosity is a reflection of both network topology and cross-linker exchange kinetics. [70][71][72] Coarse-grained slip link modeling also offers a pathway to interrogate the interactions between backbone relaxations and transient cross-linking.…”
Section: Introductionmentioning
confidence: 99%